2016
DOI: 10.1093/ije/dyw199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal micronutrient and early food supplementation on metabolic status of the offspring at 4.5 years of age. The MINIMat randomized trial in rural Bangladesh

Abstract: Background: Fetal nutritional insults may alter the later metabolic phenotype. We hypothesized that early timing of prenatal food supplementation and multiple micronutrient supplementation (MMS) would favourably influence childhood metabolic phenotype.Methods: Pregnant women recruited 1 January to 31 December 2002 in Matlab, Bangladesh, were randomized into supplementation with capsules of either 30 mg of iron and 400 μg of folic acid, 60 mg of iron and 400 μg of folic acid, or MMS containing a daily allowance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…Therefore, in mothers suffering malnutrition antioxidant deficiency may generate a situation of oxidative stress. Intervention strategies in undernourished pregnant women demonstrate that micronutrient supplementation reduces the risk of LBW ( Ota et al, 2015 ) and improves the metabolic health of children ( Ekström et al, 2016 ). Undernutrition has an impact on the placenta, leading to deficient development or reducing the enzymatic barrier 11-β-HSD, allowing for excess cortisol reaching the fetus.…”
Section: Oxidative Stress and Dohadmentioning
confidence: 99%
“…Therefore, in mothers suffering malnutrition antioxidant deficiency may generate a situation of oxidative stress. Intervention strategies in undernourished pregnant women demonstrate that micronutrient supplementation reduces the risk of LBW ( Ota et al, 2015 ) and improves the metabolic health of children ( Ekström et al, 2016 ). Undernutrition has an impact on the placenta, leading to deficient development or reducing the enzymatic barrier 11-β-HSD, allowing for excess cortisol reaching the fetus.…”
Section: Oxidative Stress and Dohadmentioning
confidence: 99%
“…MMS given without food supplementation in early pregnancy (UMMS) had the highest DALY estimates as a result of both the highest number of YLLs and YLDs. Further, in a recently published study the MINIMat trial children allocated to the multiple micronutrient supplementation displayed an unfavourable metabolic profile at 4,5 years with lower levels of IGF and HDL[ 18 ]. These results indicate positive outcomes of providing MMS only when it is combined with increased macronutrient intake that is initiated in early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MMS supplementation was related to more stunting in comparison with Fe60F, while the early invitation to food supplementation compared with the usual timing of the start of supplementation was associated with reduced frequency of stunting before the age of five years[ 17 ]. The potential negative effect by prenatal MMS on child linear growth was also supported by lower insulin-like growth factor 1 at 4.5 years in children whose mothers had been allocated to this treatment [ 18 ]. This combination of favourable and unfavourable effects illustrates that nutrition interventions may influence multiple outcomes that may be positive as well as negative from a public health perspective.…”
Section: Introductionmentioning
confidence: 99%
“…5 In Bangladesh, prenatal MMN increased the occurrence of stunting up to 5 years 6 and decreased the IGF1 levels. 7 MMN was also associated with unfavourable metabolic markers at 4•5 years. 7 These unfavourable eff ects of prenatal MMN supplementation might be context-specifi c. A systematic review and meta-analysis, published in 2016, 8 of prenatal MMN trials concluded that there is no evidence that, compared with iron and folic acid supplementation, routine maternal antenatal multiple micronutrient supplementation improves childhood survival, growth, body composition, blood pressure, respiratory, or cognitive outcomes.…”
mentioning
confidence: 92%
“…7 MMN was also associated with unfavourable metabolic markers at 4•5 years. 7 These unfavourable eff ects of prenatal MMN supplementation might be context-specifi c. A systematic review and meta-analysis, published in 2016, 8 of prenatal MMN trials concluded that there is no evidence that, compared with iron and folic acid supplementation, routine maternal antenatal multiple micronutrient supplementation improves childhood survival, growth, body composition, blood pressure, respiratory, or cognitive outcomes. 8 In view of this background of both favourable and unfavourable eff ects, the new evidence presented in the study by Prado 9 emphasises that all women, children, and adolescents should have equal opportunities to thrive and calls for a new set of global research priorities.…”
mentioning
confidence: 92%